Assessment of anti-HIV-1 guide RNA efficacy in cells containing the viral target sequence, corresponding gRNA, and CRISPR/Cas9 - Allen, Alexander G.; Chung, Cheng-Han; Worrell, Stephen D.; Nwaozo, Glad; Madrid, Rebekah; Mele, Anthony R.; Dampier, Will; Nonnemacher, Michael R.; Wigdahl, Brian (Frontiers in Genome Editing, 2023)
The CRISPR/Cas9 gene editing system has been shown to be effective at inhibiting HIV-1. Most studies have not been able to track which cells received Cas9 to understand if viral expression is due to lack of delivery or lack of targeting. Some studies have used stably transduced cells under drug selection to accomplish this goal, but this is not a therapeutically viable option. We have utilized a two-color system that allows tracking of viral protein expression and which cells received the CRISPR/cas9 system. These experiments ensured that each gRNA used was a perfect match to the intended target to remove this variable. The data showed that gRNAs targeting the TAR region or other highly conserved regions of the HIV-1 genome were effective at stopping viral gene expression, with multiple assays demonstrating greater than 95 percent reduction. Conversely, gRNAs targeting conserved sites of the 5’ portion of the U3 region were largely ineffective, demonstrating that the location of edits in the LTR matter with respect to function. In addition, it was observed that a gRNA targeting Tat was effective in a T-cell model of HIV-1 latency. Taken together, these studies demonstrated gRNAs designed to highly conserved functional regions have near 100% efficacy when delivery was tracked.